Region-specific differences in amyloid precursor protein expression in the mouse hippocampus - Del Turco, Domenico; Paul, Mandy H.; Schlaudraff, Jessica; Hick, Meike; Endres, Kristina; Müller, Ulrike C.; Deller, Thomas (Frontiers in molecular neuroscience, 2016)
The physiological role of amyloid precursor protein (APP) has been extensively investigated in the rodent hippocampus. Evidence suggests that APP plays a role in synaptic plasticity, dendritic and spine morphogenesis, neuroprotection and - at the behavioral level - hippocampus-dependent forms of learning and memory. Intriguingly, however, studies focusing on the role of APP in synaptic plasticity have reported diverging results and considerable differences in effect size between the dentate gyrus and area CA1 of the mouse hippocampus. We speculated that regional differences in APP expression could underlie these discrepancies and studied the expression of APP in both regions using immunostaining, in situ hybridization, and laser microdissection in combination with quantitative reverse transcription PCR and western blotting. In sum, our results show that APP is approximately 1.7-fold higher expressed in pyramidal cells of Ammon´s horn than in granule cells of the dentate gyrus. This regional difference in APP expression may explain why loss-of-function approaches using APP-deficient mice revealed a role for APP in Hebbian plasticity in area CA1, whereas this could not be shown in the dentate gyrus of the same APP mutants.
Gesehen am 07.05.2020